2018
DOI: 10.1155/2018/4578762
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Teaching with Humanoid Robot: A New Powerful Experimental Tool to Improve Children’s Learning Ability

Abstract: Browsing the literature shows that an increasing number of authors choose to use the learning by teaching approach in the field of educational robotics. The goal of this paper is, on the one hand, to produce a review of articles describing the effects of this approach on learning and, on the other hand, to review the literature in order to explore the characteristics at the core of this approach. We will only focus on the work using a humanoid robot. The areas of learning studied are writing, reading, vocabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…It has a clear target to assist children to learn handwriting with a social robot on the basis of learning by using a teaching approach (LbT) (Hood et al, 2015;Jacq et al, 2016;Lemaignan et al, 2016). Since the development of these studies, others have effectively employed the robot-assisted LbT approach to other fields of inquiry (Jamet et al, 2018;Yadollahi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has a clear target to assist children to learn handwriting with a social robot on the basis of learning by using a teaching approach (LbT) (Hood et al, 2015;Jacq et al, 2016;Lemaignan et al, 2016). Since the development of these studies, others have effectively employed the robot-assisted LbT approach to other fields of inquiry (Jamet et al, 2018;Yadollahi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of our "mentor-child" context 11 was tested with children between 5 and 6 in the class inclusion task and successfully made the question of class inclusion more relevant for the child when it was asked (Masson et al, 2017a;Jamet et al, 2018). We hypothesize that the "mentor-child" context should similarly decrease the ambiguity of the ToM question to make it clearer that it is a request about the mental states of the character Maxi.…”
Section: The Robot-pupil Solutionmentioning
confidence: 98%
“…Politzer observed that when he disambiguated the question of class inclusion the success of participants was significantly improved and came earlier: between 5 and 6 years-old (see also Jamet et al, 2018).…”
Section: The Ambiguity Of the Tom Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…does slightly better in some cases, as for example, if it asks about the number of children, siblings or pets, and if then the user answers “I have two,” the chatterbot will answer “What are their names?” which is an expected question, but will say the same thing if the topic is about computers instead of children (clearly indicating that this is a generic and pre-programmed reply). The lack of pragmatic processing is indeed extremely common in artificial social agents in general (Jacquet et al, 2019) despite experimental data showing its importance, including with social robots (Masson et al, 2017b; Jamet et al, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%